2005
DOI: 10.1111/j.1398-9995.2005.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+IL‐13+ cells in peripheral blood well correlates with the severity of atopic dermatitis in children

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease affecting about 15% of children, with consequent costs and morbidity. The AD has its onset during the first

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 24 publications
3
36
0
1
Order By: Relevance
“…Skin lesions, especially acute skin lesions, and even unaffected skin from patients with atopic eczema were associated with an increased expression of IL-13 mRNA [3]. The percentage of IL-13-expressing CD4+ T cells in peripheral blood mononuclear cells in patients in the acute phase of atopic eczema was significantly higher than in control subjects; also, the percentage of CD4+ IL-13+ T cells in the patient group was significantly correlated with disease severity [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Skin lesions, especially acute skin lesions, and even unaffected skin from patients with atopic eczema were associated with an increased expression of IL-13 mRNA [3]. The percentage of IL-13-expressing CD4+ T cells in peripheral blood mononuclear cells in patients in the acute phase of atopic eczema was significantly higher than in control subjects; also, the percentage of CD4+ IL-13+ T cells in the patient group was significantly correlated with disease severity [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, immunological response to allergens represents an important trigger for the increase of eosinophil counts in the peripheral blood and serum IgE level [52]. A Japanese study found that the eosinophil levels correlated with the allergic diseases, high blood eosinophil levels in atopic diseases [53]. They found that both the absolute eosinophil count and the IgE level showed significant increase with allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Recently, a higher number of IL-13-expressing CD4-bearing T cells has been observed in the peripheral blood mononuclear cells of patients with AD compared to those of healthy individuals. 21 IL-13, which is a pivotal mediator of the Th2 immune response, 22 plays an important role in the recruitment of CD4-bearing T cells through activating keratinocytes in patients with acute AD. 23 Although IL-13 is a key cytokine in AD, mechanisms of IL-13 production in AD are not fully understood.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Furthermore, patients with acutephase AD possess a higher number of IL-13-expressing CD4-bearing T cells compared to healthy individuals. 21 More importantly, keratinocytes stimulated by IL-13 highly express CCL22, and cause infiltration of CD4-bearing T cells into lesions in skin, 23 providing a pathological marker for AD or AD-like dermatitis. 3,18 Furthermore, IL-13 induced collagen protein as well as mRNA in a dose-dependent manner, 38 and higher levels of collagen were an all too common clinical feature in untreated AD patients.…”
mentioning
confidence: 99%